2000
DOI: 10.1117/12.386451
|View full text |Cite
|
Sign up to set email alerts
|

<title>Protecting the DUV process and optimizing optical transmission</title>

Abstract: It has been well documented that DUV lithographic processes are sensitive to airborne contamination such as ammonia and n-methyl-2-pyrrolidone (NMP). Chemical filtration technologies have aided in minimizing the problems associated with these contaminants in the photolithographic process. As the demand for smaller features increases, so will the need to operate within even cleaner environments than are available today. One such area where airborne contamination has proven to be of significant concern, is withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…2,11,12,16 It has been reported that the photolithographic process and the optical elements in the exposure tool can be sensitive to contaminant levels below 1 ppb. [9][10][11][12]26 Therefore, the chemical filter media must be capable of reducing the contaminant concentration below this level at the conditions expected within each area of the tool. The chemical filter must be capable of maintaining these exceptionally low levels for extended periods of time; hopefully, this meets, or exceeds the life of the tool.…”
Section: Long Term Removal Efficiency At Low Concentrationsmentioning
confidence: 99%
See 3 more Smart Citations
“…2,11,12,16 It has been reported that the photolithographic process and the optical elements in the exposure tool can be sensitive to contaminant levels below 1 ppb. [9][10][11][12]26 Therefore, the chemical filter media must be capable of reducing the contaminant concentration below this level at the conditions expected within each area of the tool. The chemical filter must be capable of maintaining these exceptionally low levels for extended periods of time; hopefully, this meets, or exceeds the life of the tool.…”
Section: Long Term Removal Efficiency At Low Concentrationsmentioning
confidence: 99%
“…8 POU chemical filters must be capable of reducing molecular contamination in gas streams to levels (typically <1 ppb) that do not compromise the photolithographic process and do not degrade the exposure tool optical elements. [9][10][11][12] These levels must be achieved while still maintaining the required environmental specifications at each location within the tool. For example, within the wafer stage a low level of moisture, acidic, basic and organic contaminants is required in order to both protect optical coatings and allow maximum light transmission.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations